REMUNERASI DAN RASA KEADILAN MASYARAKAT - Martini, Rina (Faculty of Social and Political Sciences Diponegoro University, 2011)
Abstract:The acceptance of remuneration allowance for civil servants or members of bureaucracy has disturbed people's sense of justice. It is due to services performances that still unwell managed, and many of our people still live in bad condition, such as malnutrition, unemployment, broken school buildings, and poverty. Therefore, civil bureaucrats should balance it with real actions. In particular they must be friendly, uncorrupt, and unpicky. While in general, civil bureaucrats should improve their performances in each functions and duties, either as village or sub-dictrict apparatus, police, military, in legal, and so forth. Those steps should be accompanied by a spesific performance evaluation's parameters and community involvement.Keywords :remuneration, sense of justice, performance reforms permalink: http://ejournal.undip.ac.id/index.php/forum/article/view/3159